The Influence of Entrepreneurship, Business Strategy, and Business Networking on Competitive Advantage in Micro, Small and Medium Enterprises in the FnB Industry in Jabodetabek - Hutabarat, Zoel; Gianina, Gianina (Universitas Pelita Harapan, 2023)
This research examines the impact of Entrepreneurship, Business Strategy and Business Networking for Competitive Advantage on small medium enterprises in FnB industry in Jakarta, Bogor, Depok, Tangerang, and Bekasi. This research uses quantitative research methods and purposive sampling. Total respondents in this research is 201 respondents from Jabodetabek area. The spread of the quationnaire is done using Google Form. Analysis and testing of statistical data in this research is using SmartPLS4 application. The result of this research study stated that entrepreneurship has an influence on business strategy, entrepreneurship has an influence on competitive advantage, business strategy han an influence on business networking, and business networking has an influence on competitive advantage. While business strategy doesn’t has influence on competitive advantage.